HUBUNGAN MOTIVASI MAHASISWA DIV BIDAN PENDIDIK UNTUK MENYELESAIKAN SKRIPSI DENGAN KETEPATAN WAKTU MAJU PROPOSAL - Puspawati, Cok lstri Putri Prigita; Purnomo, Eddy; Sumarah, Sumarah (Poltekkes Kemenkes Yogyakarta, 2015)
D-lV Midwife Educator students must complete a thesis as a requirement of graduation. High motivation improves the punctuality to present the proposal. ln a preliminary study at STIKES Aisyiyah Yogyakarta, 27% of the students who presented the proposal on time and 5 of 7 people interviewed had low motivation to complete the thesis. Objective to determine the correlation between motivation to complete the thesis and the punctuality to present the proposal of STIKES 'Aisyiyah Yogyakarta. Methods This study used a descriptive-analytic design with a cross-sectional approach. The population was 130 people with a-sample of gg people. Thesampling technique was Proportional to Random Sampling. The sampling technique in the field used Accidentat Random Slampting. Dala analysis was univariate and bivariate with Spearman Rank Correlation (Cl 5%). Spearman Rank Correlation test showed p- value 0.00. The correlation value was 0.567 with a positive correlation. Students who had high motivation who presented the proposal on time was 82.35%. Conclusion Motivation to complete the thesis affects the punctuality to present the proposal.